Hydrogel co-loading SO2 prodrug and FeGA nanoparticles for enhancing chemodynamic therapy by photothermal-triggered SO2 gas therapy - Huang, Qinqin; Lyu, Meng; Tang, Wenxue; Qi, Pengyuan; Hu, Hongzhi (Frontiers in Bioengineering and Biotechnology, 2022)
Chemodynamic therapy (CDT) is an effective anti-tumor method, while CDT alone cannot achieve a good therapeutic effect. Moreover, the overexpression of glutathione (GSH) in tumor cells dramatically limits the efficiency of CDT. Here, we proposed a hydrogel co-loading SO2 prodrug and FeGA nanoparticles (NPs) for enhancing CDT by photothermal-triggered SO2 gas therapy (FBH) system by mixing benzothiazolyl sulfonates (BTS) and FeGA NPs in a certain ratio and encapsulating them in a heat-sensitive hydrogel. FeGA NPs could accelerate the release of Fe2+ under acidic conditions and light, and combine with excess H2O2 in the tumor for chemokinetic treatment. BTS, as a water-soluble prodrug of SO2, can accurately control the release of SO2 gas by virtue of the excellent photothermal conversion ability of FeGA NPs and the acidic pH value of tumor site. SO2 can not only induce cell apoptosis, but also consume excess GSH in cancer cells and increase the content of reactive oxygen species, which seriously destroyed the redox balance in cancer cells and further promotes the therapeutic effect of Fenton reaction. The intelligent FBH system provided a new approach for the synergistic treatment of CDT and SO2 gas, which demonstrated good anticancer effects both in vivo and in vitro.